Study of the Efficiency of the Magnetic Deflector at Various Operation Conditions - A. Aziz, Shahad; A. Hussein, Oday (Al-Nahrain Journal of Science, 2025)
The efficiency of the magnetic deflector for variation operation condition was investigated. The design appears that the possibility of finding the constant characteristics of the deflector which lead to stability in the properties of the electron beam at the image plane despite the change in the properties of the electron source as: the initial beam divergence and the energy. The relation between the value of applied magnetic field on the magnetic deflector and the properties of the electron beam was studied. also the distribution of different value of the energy of the electron beam was studied. The calculation was carried out for different values of the divergence angle. The result showed that the increases in divergence angle dose not result change in the nature of the distribution of energy of the electron beam at image plane, and one can find constant dimensions of the electron beam at image plane even though the electron beams energy was altered, and this results can be achieved by choosing the appropriative values of magnetic field to be applied to the deflector. The calculations showed that the non-linear relation between the amount of the magnetic field and values of the kinetic energy electron beam.